Analisis Kebijakan Sumber Daya Alam Provinsi Sumatera Utara - Purba, Bonaraja; Tarigan, Desry Rasmita; Ginting, Renata Olivia (Economic Reviews Journal, 2024)
This research aims to analyze the influence of natural resource policies on economic growth and environmental benefits in North Sumatra Province. The research methods used include literature studies, interviews with stakeholders, secondary data analysis, quantitative analysis, and formulation of policy recommendations. The results of the analysis show that the implementation of natural resource policies has a significant impact on economic growth, but also raises challenges related to environmental protection and fair distribution of benefits. Policy recommendations are prepared to strengthen sustainability aspects in natural resource management in North Sumatra Province.